Saving the planet through consumption: an analysis of the discourse behind Uber Planet in Brazil - Costa, Thiago (Comunicologia, 2025)
This paper analyzes the discourse of cause-related marketing (CRM) employed by the app Uber to promote its “Uber Planet/Green” initiative, which aims to offer more sustainable and eco-friendly transportation options. The research examines consumer practices through a psychoanalytic lens (LACAN, 1999; STAVRAKAKIS, 2007; ŽIŽEK, 2000, 2008), along with extensions such as Rifkin’s concept of cultural capitalism (2000) and the practice of “causumerism” by Richey and Ponte (2011). The methodology involves a critical analysis of marketing campaigns and impact reports to understand their implications. The findings indicate that, while CRM advocates for significant social causes, it also commodifies social activism, aligning with contemporary critiques of ethical consumption and the practices of comfort and authenticity (BANET-WEISER, 2012). This research contributes to the discourse on the complexities of consumer engagement with sustainability initiatives.